2022
DOI: 10.3390/molecules27238328
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Nicotiana tabacum Leaves: Optimization of Extraction Yield and Nicotine Content

Abstract: The employment of supercritical carbon dioxide extraction for obtaining the chemical compounds from N. tabacum leaves, especially nicotine, is advancing. The supercritical carbon dioxide extraction of dried N. tabacum cv. Samsun and N. tabacum cv. Virginia at different process parameters was performed to obtain the highest extraction yield and nicotine relative amount. The optimal extraction conditions concerning the highest extraction yield and nicotine relative amount were determined by response surface meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The highest extraction rate, 0.49%, was obtained by extracting tobacco rhizome powder dispersed with five times the volume of 90% ethanol at 65 °C and 25 MPa. Compared to tobacco leaves, which contain about 3% nicotine [ 13 ], Zimbabwean tobacco roots contain only one-sixth of the amount of nicotine found in tobacco leaves. Previous studies have shown that 50 °C is the optimal temperature for the extraction of nicotine from tobacco by SC-CO 2 [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest extraction rate, 0.49%, was obtained by extracting tobacco rhizome powder dispersed with five times the volume of 90% ethanol at 65 °C and 25 MPa. Compared to tobacco leaves, which contain about 3% nicotine [ 13 ], Zimbabwean tobacco roots contain only one-sixth of the amount of nicotine found in tobacco leaves. Previous studies have shown that 50 °C is the optimal temperature for the extraction of nicotine from tobacco by SC-CO 2 [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to tobacco leaves, which contain about 3% nicotine [ 13 ], Zimbabwean tobacco roots contain only one-sixth of the amount of nicotine found in tobacco leaves. Previous studies have shown that 50 °C is the optimal temperature for the extraction of nicotine from tobacco by SC-CO 2 [ 13 , 32 ]. However, in this experiment, the nicotine yield did not stabilise until the temperature reached 60–65 °C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations